4th National Conference on Key Performance Indicators - National Conference on Key Performance Indicators 2005 : Kuala Lumpur); Persatuan Alumni Pegawai Tadbir dan Diplomatik; Uni-Link Smart Venture Sdn. Bhd. ([Kuala Lumpur] : Persatuan Alumni Pegawai Tadbir dan Diplomatik, 2005)
Discusses on key performanca indicator (KPI) framework in the public and corporate sector, linking KPI to management and leadership, issues-based KPIS, its strategies and solutions, KPI case study in public and corporate sector and also international exchange on good practice of KPI
Keywords: Performance technology -- Congresses; Performance standards -- Congresses; Organizational effectiveness